2024
DOI: 10.1039/d4nr00973h
|View full text |Cite
|
Sign up to set email alerts
|

An insight, at the atomic level, into the structure and catalytic properties of the isomers of the Cu22 cluster

Huimin Zhou,
Tao Yang,
Huijuan Deng
et al.

Abstract: The study of structural isomerism in copper nanoclusters has been relatively limited compared to gold and silver nanoclusters. In this work, we present the controlled synthesis and structures of two...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Exclusive examination of these reactions reveals a spectrum ranging from intricate solvochemical processes to cutting-edge electrocatalysis. Their meticulously crafted structural architecture and distinctive surface properties, combined with the reduction potential of Cu atoms, empower them to catalyze reactions with exceptional efficiency and selectivity in various chemical contexts. Nevertheless, it has been observed that numerous factors influence the control of their structural architecture and surface characteristics. Alterations in their structural configuration also lead to specific changes in their photophysical properties, a widely discussed aspect attributed to their atomic confinement. , …”
Section: Introductionmentioning
confidence: 99%
“…Exclusive examination of these reactions reveals a spectrum ranging from intricate solvochemical processes to cutting-edge electrocatalysis. Their meticulously crafted structural architecture and distinctive surface properties, combined with the reduction potential of Cu atoms, empower them to catalyze reactions with exceptional efficiency and selectivity in various chemical contexts. Nevertheless, it has been observed that numerous factors influence the control of their structural architecture and surface characteristics. Alterations in their structural configuration also lead to specific changes in their photophysical properties, a widely discussed aspect attributed to their atomic confinement. , …”
Section: Introductionmentioning
confidence: 99%